Community-Driven Health Priorities for Healthy Aging With HIV. (January 2019) - Brown, Brandon; Marg, Logan; Cabral, Alejandra; Didero, Michelle; Christensen, Christopher; Taylor, Jeff; Subica, Andrew
Abstract : Abstract: Palm Springs, CA, is a retirement community with the highest prevalence of gay men living with HIV older than 50 years in the United States. Through a community–academic partnership, we explored the major health issues, resiliencies, and priority research topics related to HIV and aging. We conducted five community facilitated focus groups with different stakeholders, including two focus groups with older adults living with HIV, one with their caregivers, one with HIV-focused community-based organizations, and a joint focus group with researchers and HIV care providers. Using the rigorous and accelerated data reduction technique, five major themes emerged, which included long-term side effects of medication, social determinants of health, mental health, resiliencies, and involving community in research. These data are important for developing effective interventions, conducting useful and impactful research, and providing health care providers with the tools and knowledge to provide optimal care. Abstract : Supplemental Digital Content is Available in the Text.